2016
DOI: 10.1128/jcm.00376-16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Laboratory Implementation of Verigene BC-GN Microarray-Based Assay for Detection of Gram-Negative Bacteria in Positive Blood Cultures

Abstract: c Gram-negative bacteremia is highly fatal, and hospitalizations due to sepsis have been increasing worldwide. Molecular tests that supplement Gram stain results from positive blood cultures provide specific organism information to potentially guide therapy, but more clinical data on their real-world impact are still needed. We retrospectively reviewed cases of Gram-negative bacteremia in hospitalized patients over a 6-month period before (n ‫؍‬ 98) and over a 6-month period after (n ‫؍‬ 97) the implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 30 publications
3
81
0
1
Order By: Relevance
“…Although patients with a history of and risk factors for MDROs were carefully evaluated, absence of susceptibility data at the time of organism identification made streamlining of therapy particularly challenging. Walker et al demonstrated that detection of resistance markers via Verigene BC-GN assay was valuable and optimized antimicrobial regimens faster, resulting in a significantly shorter ICU LOS (16.2 versus 12.0 days; P ϭ 0.03) and a decreased 30-day mortality rate (19.2 versus 8.1%; P ϭ 0.04), particularly for patients infected with extended-spectrum beta-lactamase-producing bacteria (20). The significant cost sav-ings demonstrated in this study, as well as several others (8,21,22), may justify obtaining additional technology with the ability to detect resistance markers in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with a history of and risk factors for MDROs were carefully evaluated, absence of susceptibility data at the time of organism identification made streamlining of therapy particularly challenging. Walker et al demonstrated that detection of resistance markers via Verigene BC-GN assay was valuable and optimized antimicrobial regimens faster, resulting in a significantly shorter ICU LOS (16.2 versus 12.0 days; P ϭ 0.03) and a decreased 30-day mortality rate (19.2 versus 8.1%; P ϭ 0.04), particularly for patients infected with extended-spectrum beta-lactamase-producing bacteria (20). The significant cost sav-ings demonstrated in this study, as well as several others (8,21,22), may justify obtaining additional technology with the ability to detect resistance markers in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid identifi cation of GN bacteremia and key susceptibility markers can lead to many benefi ts, such as earlier deescalation of empiric therapy and switch to appropriate targeted antimicrobials that can lead to better patient outcomes, decreased length of hospital stay, and decreased overall hospital costs (9)(10)(11)(12). Th e Verigene BC-GN assay has two major advantages favoring its routine use: a random-access format with very limited handson time and the ability to rapidly provide clinically actionable therapeutic information to physicians.…”
Section: Discussionmentioning
confidence: 99%
“…96 The authors compared two periods, in which standard procedures for species identification and susceptibility testing were in place alone or in combination with the Verigene BC-GN assay. The amplification assay was performed immediately after the blood culture bottles were flagged positive, and results were directly reported.…”
Section: Clinical Impact Of Amplification-based Diagnosticsmentioning
confidence: 99%